Surgical treatment of patients with shoulder joint stiffness and injury to the glenoid labrum - Sergiienko, R.O.; Vovchenko, G.Ya.; Yuriychuk, L.; Satyshev, M.M.; Bursuk, Yu.Ye.; Olifirenko, O.I. (TERRA ORTHOPAEDICA, 2023)
Background. Most of our colleagues, upon discovering injuries to the glenoid labrum or other soft tissue structures of the shoulder joint in a patient, perform surgical interventions without paying attention to changes in its capsule. Objective: to compare the treatment outcomes of patients with shoulder contracture who underwent arthroscopic capsular release with re-fixation of the glenoid labrum versus those who underwent only re-fixation of the glenoid labrum.Materials and methods: The study included 98 patients with shoulder joint stiffness and glenoid labrum injury. The patients were divided into two groups: group 1 underwent re-fixation of the glenoid labrum and arthroscopic capsular release, while group 2 underwent re-fixation of the glenoid labrum without arthroscopic capsular release.Results: Three months after the operation, in group 2, the mean functional outcome according to the Constant Shoulder Score scale was slightly worse than in group 1 and ranged from 14.5 ± 6.2 points, while in group 1, the mean functional outcome was 8.5 ± 6 points (p = 0.031). Six months after the operation, in group 1, the mean functional outcome according to the Constant Shoulder Score scale was 5.1 ± 5.6 points, while in group 2, it was 10.1 ± 4.1 points (p = 0.024). Conclusion: The results of treating patients with secondary shoulder stiffness who underwent arthroscopic capsular release and fixation of the glenoid labrum were better according to the Constant Shoulder Score and the VAS scale at both 3 and 6 months after the operation than the results of treating patients who underwent only fixation of the glenoid labrum without arthroscopic capsular release.